Revolutionizing Legal Education: Embracing Technology to Equip Students for Success in the Digital Age - Mochammad Tanzil Multazam (Borneo Educational Journal (Borju), 2020)
The legal profession is changing as law schools embrace technology to prepare students for 21st-century concerns. This study covered legal education's technological initiatives, including online training, blended learning, adaptive learning materials, and online mentorship programs. This study aims to provide a detailed review of legal education's technological innovations and their effects on the legal profession. We examined online education, including synchronous and asynchronous distance learning and Massive Open Online Courses (MOOCs), which provide students flexibility and convenience. Blended learning lets law professors use educational videos and other internet resources to make learning more engaging and effective. Technology is revolutionizing legal education and preparing students for the digital age. Law schools may prepare students for a future where technology will be increasingly crucial by adopting new tools and instructional approaches. The study stressed the necessity for forward-thinking legal education and keeping up with legal business technology.